Analysis of Risk Factors for Chronic Energy Deficiency in Pregnant Women - Lia Marshanda; Sulastri Sulastri (GLOBAL HEALTH SCIENCE GROUP, 2026)
Chronic energy deficiency is a nutritional problem that is still commonly experienced by pregnant women in developing countries. This condition occurs when energy and protein intake is not met over a long period of time. CED is usually identified through upper arm circumference (UAC) measurements, where a value of <23.5 cm or in the red area of the UAC tape indicates risk. This study aims to identify risk factors associated with the occurrence of CED in pregnant women. The method used is quantitative with a cross-sectional design. The study population consists of all pregnant women who underwent examinations at the Gambirsari Surakarta Community Health Center in August 2025, with a sample of 88 respondents determined through consecutive sampling. Data were obtained through questionnaires and interviews, with the validity of the knowledge questionnaire ranging from 0.341 to 0.664, thus declared valid (r ≥ 0.30) and reliability tested with a Cronbach's Alpha value of 0.885, indicating excellent reliability. In contrast, the GPAQ instrument had substantial reliability (Kappa 0.67–0.73) and acceptable criterion-related validity against accelerometer (r = 0.48). Based on the results, the majority of participants did not experience CED (61.4%), were aged 20–35 years (83%), had a parity of <2 (94.3%), were economically well-off (60.2%), had good knowledge (59.1%), and engaged in light physical activity (43.2%). The chi-square analysis drew a significant relationship among age and CED (p=0.001), parity (p=0.05), economic status (p=0.001), knowledge (p=0.001), and physical activity (p=0.001). The multivariate test results confirmed that knowledge (p=0.002, OR=1.066) and physical activity (p=0.005, OR=1.226) were the dominant factors. There was a significant relationship among age, parity, economic status, knowledge, and physical activity by CED in pregnant women. Multivariate analysis confirmed that knowledge and physical activity were the dominant factors influencing the incidence of CED.